Enhancing Social Skills in Islamic Religious Education at the Junior High School Level: A Differential Instruction Approach - Alhamuddin, Alhamuddin; Muhamad Arif Nugraha (Program Pascasarjana Universitas Ibrahimy, 2024)
This research aimed to see how the cultivation and improvement of students' social skills through a differentiated instruction approach. The research approach uses quantitative with quasi-experimental method. Data collection is done by reviewing documents, interviews with related parties, especially teachers and students related to social skills and differentiated instruction approaches. Observation was used to see the development of social skills and learning. Questionnaires are used to see how the development of students' social skills after learning with a differentiated approach, these resulted are combined with observation results. The resulted showed that differentiated instruction is conducted by conducting a needs analysis of students' learning styles in the classroom. Then, the teacher analyses the results and determines the strategy that suits the students' learning styles to be used in delivering the material. The presentation is used with a variety of methods and techniques that facilitate students' learning styles. So, the results showed that this approach has a significant effect on improving students' social skills. Suggestions for future researchers, conduct further research with a larger population and different types of learning styles